Oral Burn by acidental acid ingestion: Case report (Research, Society and Development, 2021)
Introduction: Burns of the oral mucosa can be caused due to thermal, chemical or electrical trauma, which can cause a severe lesion not only in the oral mucosa, but also in the esophagus and stomach, leading to tissue necrosis or even perforation of the structures. Objective and case report: This article aim is report a clinical case of accidental ingestion of acidic substance and perform a literature review discussing the importance of the dental surgeon in the multidisciplinary team of an emergency service, acting in the diagnosis and treatment of injuries of chemical burns. Conclusion: Something indispensable for the restoration of proper function and recovery of these patients.